2019
DOI: 10.5130/ijcre.v12i1.5894
|View full text |Cite
|
Sign up to set email alerts
|

Ethical collaboration and the need for training: Partnerships between Native American Tribes and climate science organisations

Abstract: Indigenous peoples develop and utilise climate science resources to address climate change impacts, and climate scientists often collaborate on such projects. Little is known about whether climate science organisations (CSOs) adequately train their staff to work ethically with Indigenous peoples, promoting benefits for Tribes while reducing harms. To research this training, we conducted interviews with CSO employees (n=9) and Native American Tribal citizens (n=7). Thematic content analysis revealed that many c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Research on climate collaborations directly between Native Nations and federal agencies has demonstrated the need for climate scientists to receive ethics training before engaging tribal collectives (Kirby et al, 2019). It aims to keep scientists from undermining tribal sovereignties (Kalafatis et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Research on climate collaborations directly between Native Nations and federal agencies has demonstrated the need for climate scientists to receive ethics training before engaging tribal collectives (Kirby et al, 2019). It aims to keep scientists from undermining tribal sovereignties (Kalafatis et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Further, important power dynamics have been uncovered in partnerships between Native American communities and climate science organizations (Kirby et al, ). Native American communities more often identified challenges in their partnerships with climate science organizations, while climate science organizations more often identified the benefits of these partnerships (Kirby et al, ). This observation represents a striking parallel to the power‐laden geographical mismatch that we have seen in climate change adaptation literature focusing on equity, and it suggests ongoing colonization in knowledge production by the Global North (Todd, ).…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, it has even been suggested that the Anthropocene as a whole, and its associated knowledge production, is a continuation of colonial dispossession and disempowerment (Davis & Todd, 2017). Further, important power dynamics have been uncovered in partnerships between Native American communities and climate science organizations (Kirby et al, 2019). Native American communities more often identified challenges in their partnerships with climate science organizations, while climate science organizations more often identified the benefits of these partnerships (Kirby et al, 2019).…”
Section: Blind Spotsmentioning
confidence: 99%
“…Rather than engage in another effort to interview community residents, we elected to engage community-identified experts in a co-analysis of the existing information. This approach is part of a shift in the role of community participants from providers of information to interpreters of information, and part of a wider movement towards meaningful collaborations, Indigenous leadership in research, and the co-production of knowledge, a paradigm emphasizing the need to work together from start to finish in research projects (Lemos and Morehouse, 2005;Bartlett et al, 2012;Meadow et al, 2015;Whyte, 2017;David-Chavez and Gavin, 2018;Peltier, 2018;Kirby et al, 2019). The aim of the study and of this paper therefore is not to generate or report new observations and basic information, but to take a new look at what is already on record, to better understand the meanings and implications of that existing information from the perspective of Indigenous communities.…”
Section: Introductionmentioning
confidence: 99%